2006
DOI: 10.1111/j.1467-6486.2006.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Firm R&D Investment and Environment on Acquisition Likelihood*

Abstract: R&D investments contribute to the development of firm technology resources, and the possession of such resources often increases a firm's attractiveness as a potential acquisition target. However, the value ascribed to a firm's technology resources by would-be acquirers may be moderated by its industry's environmental characteristics. Using data from 2886 firms, we find that investments in R&D predict acquisition likelihood and that R&D investments are most strongly associated with acquisition of firms under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 118 publications
3
109
0
Order By: Relevance
“…Results on the profitability of size relatedness are mixed. Some authors Finkelstein and Haleblian 2002;Heeley et al 2006;Kumar 1985;Papadakis 2005;Ravenscraft and Scherer 1989;Slangen 2006) find evidence for increased profitability when both buyer and target are of similar size.…”
Section: Size Relatednessmentioning
confidence: 99%
“…Results on the profitability of size relatedness are mixed. Some authors Finkelstein and Haleblian 2002;Heeley et al 2006;Kumar 1985;Papadakis 2005;Ravenscraft and Scherer 1989;Slangen 2006) find evidence for increased profitability when both buyer and target are of similar size.…”
Section: Size Relatednessmentioning
confidence: 99%
“…Many of these characteristics fit the classic profile of a distressed (or value) stock. Heeley, King, and Covin (2006) found that higher R&D spending increases the likelihood of being acquired for all firms that report R&D expenditures, but they do not control for the effects of industry variation in R&D spending. Desyllas and Hughes (2009) found that R&D predicts the likelihood of being acquired, but they limited their analysis to R&D productivity as measured by patent intensity.…”
Section: Review Of the Studies On The Likelihood Of Being Acquiredmentioning
confidence: 88%
“…Since R&D intensity contributes to growth, it may make firms more appealing targets. Heeley et al (2006) find a positive relation between a firm's R&D "stock" (a proxy for the current value of trailing R&D expenditures) and the likelihood of being acquired. Desyllas and Hughes (2009) found that R&D is positively related to the likelihood of being acquired, but they focus on patents and patent productivity as the key factors in acquisition likelihood.…”
Section: Research and Development (Randd) Expendituresmentioning
confidence: 94%
“…The theory further postulates that organizations have varying degrees of dependency on resources from the external environment, consequently, inadequate control of the external environment may interfere with the achievement of organizational goals and ultimately threaten the very existence of such organizations (Heeley, King, & Covin, 2006). The theory further states that an organization can increase its management of the external environment through the following strategies: altering "organizational interdependence" through integration or diversification; establishing collective structures to form a "negotiated environment"; and using legal, political or social action to form a "created environment" (Pfeffer & Salancik, 1978).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The theory then introduces the element of high firm power, as a key strategy in managing the external environment and ensuring resource flows. The ability of a firm to manage the external environment to its advantage is sought because of the power and control possibilities inherent in the state of dependency and uncertainty (Heeley et al, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%